Some Novel Mutants of Saccharomyces cerevisiae Inhibited by Adenosylmethionine and Adenosylhomocysteine - Spence, Kemet D. (1967)
These investigations have established the existence of a novel type of non-nutritional mutant (ai) which is inhibited in the presence of two naturally occurring cellular compounds. The inhibition is complete at an extracellular concentration at least as low as 0.05 μmole/ml of either adenosylhomocysteine or adenosylmethionine. It is suggested that adenosylhomocysteine is the true inhibitor. The ai mutants are phenotypically indistinguishable from the wild type in the absence of inhibitors. The results have shown that, if any direct effect on the methionine biosynthetic pathway exists, it is a secondary rather than the primary effect of the inhibitors. The ai mutation does not involve the loss of the adenosylmethionine (or methylmethionine): homocysteine methyltransferase. In addition, the ai mutants accumulate, maintain, and utilize adenosylmethionine and methionine in a manner similar to the parental strain. No genetic relationship could be detected between the ai-1 mutation and several different markers affecting methionine biosynthesis. The ai-1 mutation was also shown to be genetically recessive. Methionine partially reverses the inhibition caused by adenosylmethionine or adenosylhomocysteine. Neither methylmethionine nor homocysteine reversed the inhibition, which showed that the homocysteine methyltransferase cannot catalyze the synthesis of sufficient methionine under these conditions to simulate the effects of extracellularly supplied methionine. If adenine is present, methionine does not cause reversal of inhibition due to adenosylmethionine or adenosylhomocysteine. From the data presented, it is clear that the ai mutation involves some metabolic control mechanism, though the alteration does not appear to be associated primarily with the biosynthesis of methionine.